The Impact of Husband’s Perception and Value towards Family Purchase Decision Patterns - Wibisono, Christian (Journal of Economics and Behavioral Studies, 2013)
Changes are occurring in society’s norm structure. One of these changes is the shifting of women roles. More wives are working outside home and acting as a source of income, event becoming chief wage earner in the family. Many past researches have used demographic and family structure as predictor of family purchase decision patterns. This study will figure out the impact of husbands’ perception and value to the usage of wife’s income for family expenditure. Total 112 husbands in Jakarta and Bandung participated in this survey. This study used questionnaire to gather data. Questions to measure perception and norm of husbands were derived from qualitative study, a preliminary interview with 20 husbands in Jakarta and Bandung Indonesia. Schwartz Value Scale was used to measure husband’s value structure. Findings indicate that husband perception and value have significant impact on usage of wife’s income for family expenditure. This research is useful to fill the research gap in family purchase decision theory. For marketers and business practitioners the results will enhance their comprehension in segmenting, selecting more effective target and creating more creative communication strategy.